The Predictors of State and Trait Anxiety Among Healthcare Workers During the Coronavirus Disease 2019 Pandemic in Iran: A Cross‐Sectional Study - Azam Sharifi; Masoud Fallahi‐Khoshknab; Shamaneh Mohammadi; Mashaallah Zeraati Nasrabadi; Zahra Jamshidi; Mohsen Aghabeygi‐ Arani; Nilofar Mirzaei; Negin Fallahi‐Khoshknab; Parisa Rasouli; Abbas Ebadi (Health Science Reports)
ABSTRACT Background and Aims Healthcare workers (HCWs) are in contact with patients afflicted by coronavirus disease 2019 (COVID‐19). The high communicability of COVID‐19 and its different challenges cause varying levels of anxiety for HCWs. The aim of this study was to assess the predictors of state and trait anxiety among HCWs during the COVID‐19 pandemic in Iran. Methods This cross‐sectional descriptive‐analytical study was conducted in 2021–2022. Participants were 628 HCWs purposively recruited from educational hospitals in Iran. Data were collected through a demographic and occupational characteristics questionnaire and the State Trait Anxiety Inventory and were analyzed through the SPSS software (v. 23.0). Results Most participants were female (70.8%), married (67.4%), and nurses (69.7%), and had a bachelor's degree (64.0%). The means of their age and clinical work experience were 34.69 ± 6.28 years and 9.22 ± 3.98 years, respectively. Most participants suffered from moderate to very severe state (91.7%) and trait (81.2%) anxiety. The mean scores of state and trait anxiety had significant relationship with gender and employment type (p < 0.05) and the mean score of state anxiety had significant relationship with marital status and work shift (p < 0.05). Employment type and work shift significantly predicted 15% of the total variance of the mean score of state anxiety. Conclusion Most HCWs in Iran suffered from moderate to very severe state and trait anxiety during the COVID‐19 pandemic. Strong psychological support is essential for HCWs during epidemics.